(untitled) (Довкілля та здоров’я, 2020)
Objective: to determine the dependence of the indicators of students’ health on the sanitary-hygienic conditions and the organization of training in urban and rural SEI. Methods: sanitary and hygienic examination; epidemiological method with the application of sanitary-statistical, mathematical and sociological analysis. Results: Our studies demonstrate that the material and technical basis of urban and rural SEI has not changed significantly over the last 20 years and does not meet the hygienic requirements (equipping with services and utilities - water supply, heating, sewerage; in architectural-and-planning decisions - set of premises, lighting, ventilation) in 72% of cases. It is especially concerned with the rural SEI, where there are no gymnasiums in 36%; assembly halls in 67%; training computer rooms in 69%. Due to the organization of the grades for the children six years of age on the basis of existing school premises, the index of actual occupancy of the SEI exceeds the design level by 26.7% in urban SEI and by 4.5% in rural SEI, which has resulted in a two-session training regime. Nowadays, only one-fifth of the first-grade students in Ukraine, i.e. about 22%, have necessary conditions for stay and study, and the rest, almost 78% of the first-year students study at SEI where there are no such conditions. In mentioned SEI, the data of statistical reporting and medical records of 49,193 students, have been studied and analyzed in details. The number of the children with functional disorders in health state (II and III health groups) is naturally higher in all age groups of surveyed students who studied at SEI with unsatisfactory sanitary-hygienic conditions and the organization of educational process in comparison with the similar indicators in their peers who studied under optimum conditions. Dependence of health indicators of the children on the conditions and organization of training at school has been substantiated. The proportion of sick students in 2nd, 5th and 7th grades with satisfactory conditions was lower in comparison with the similar grades where these conditions were unsatisfactory (13.3% vs. 15.8% (p